Addition of propolis to milk improves lactating lamb's growth: Effect on antimicrobial, antioxidant and immune responses in animals - Cecere B.G.O.* (2021)
© 2020 Elsevier B.V.This study evaluated the effects of propolis extract, mixed in milk, on growth as well as on antimicrobial, antioxidant and immune responses in lactating lambs. Thirty-six Lacaune lambs [males; 7.0 ± 1.2 day (d) of age; 4.9 ± 0.80 kg of body weight (BW)] were assigned to the following groups: T0, T150, T200 and T250, representing 0, 150, 200, and 250 μL of propolis/kg of BW/d, respectively. All dosages (T150, T200, and T250) significantly increased weight gain (P = 0.01) with the greatest increase observed in T150 lambs (0.174, 0.244, 0.213, and 0.200 kg/d for T0, T150, T200, and T250, respectively). On regression analysis, the optimal dosage for improving weight gain was 137 μL of propolis/kg of BW/d. All dosage increased (P = 0.05) serum concentrations of total protein on d 10, but only T250 increased it on d 30. Only T150 increased (P = 0.02) the serum concentration of albumin on d 10, and all dosages increased it on d 30. The T200 tended to increase (P = 0.09) the serum concentration of immunoglobulin A, and T150 and T200 tended to increase (P = 0.09) the concentration of immunoglobulins heavy-chain. The T200 and T250 increased the concentration of transferrin on d 10 and only T250 increased it on d 42 (P = 0.01). All dosages increased (P = 0.04) the serum concentration of glucose. No effects were detected (P ≥ 0.11) for globulin, IgG light-chain, ceruloplasmin, urea, triglycerides, cholesterol, aspartate aminotransferase, or gamma-glutamyltranspeptidase. All dosage decreased (P = 0.01) the serum concentration of reactive oxygen species on d 30; however, only T150 and T200 decreased it on d 42, and the greatest reduction was observed for T150. All dosages increased (P = 0.01) nitric oxide levels on 30; however, only T150 and T200 increased them on d 42. All dosage decreased (P = 0.01) the concentration of superoxide dismutase. All dosages increased (P = 0.01) the concentration of non-protein thiols and protein thiols, with the greatest effects detected for T250. All dosages decreased (P = 0.01) counts of E. coli and total coliform counts in feces, with the greatest effects observed for T150 and T200. Taken together, the data suggest that addition of propolis to milk increased growth as well as antimicrobial, antioxidant, and immune responses in lactating lambs. The greatest effects were observed for the dosage of 150 μL of propolis/kg of BW/d.